Gynecomastia as a presenting symptom of Graves' disease in a 49-year-old man. (1st April 2021) - Mohammadnia, N; Simsek, S; Stam, F
Abstract : Summary: Gynecomastia is a symptom with a potential high disease burden. It has a variety of underlying causes, such as malignant, drug-related or hormonal. The presence of gynecomastia can be explained in thyrotoxicosis due to a concomitant disbalance of sex hormones. Interestingly, it rarely is the presenting symptom of Graves' disease. A 49-year-old man presented to our outpatient clinic with right-sided gynecomastia. After thorough history taking, more symptoms of thyrotoxicosis were present. Treatment was started with thiamazole and later levothyroxine. Three months after this treatment the gynecomastia and other symptoms resolved completely. A disbalance of sex hormones due to an increased expression of the protein sex hormone-binding globulin (SHBG) caused by thyrotoxicosis could result in gynecomastia. In vitro and in vivo research in mice suggest that the pathophysiology of thyrotoxicosis-associated gynecomastia is due to upregulation of hepatocyte nuclear factor-4α (HNF4A) in liver cells. Subsequent increase of SHBG results in a decrease of free testosterone levels. Learning points: Gynecomastia is a common finding (up to almost 40%) on physical examination in patients with hyperthyroidism. In gynecomastia, thyroid function tests should be examined on initial presentation because of the relative simple treatment. The pathophysiology of thyrotoxicosis-associated gynecomastia is well understood by a sex-hormonal disbalance due to an increased expression of SHBG. Due to the well explainable pathophysiology, reduction of symptoms can be expected after treatment. The underlying mechanism of an increased expression of SHBG is not well understood. However, in vitro and in vivo research in mice suggests that thyrotoxicosis causes an increased expression of HNF4A in liver cells. Thus, upregulating the expression of SHBG. Interestingly, HNF4A is suspected to play an important role in MODY. Future research will clarify the importance of this gene and might open up new insights for therapy.